The narrative of the City Museum : Brasília inscribed on stone - Soares, Eduardo Oliveira (2017)
The Three Powers Square, in Brasília, houses the City Museum, a building that is listedmonument both locally and nationally. The monument-museum was designed by OscarNiemeyer in 1958 and inaugurated in 1960 with the purpose of being a Place of Memory. Itscollection is composed of cuneiform texts that present a narrative about the process thatoriginated the city and the persons who made it viable. In visiting the museum, one accesses anarrative that influences the evaluation of one's own experience as an individual and participantof the society. Thus, this record of the past also contributes to the construction of an individualand collective memory. In order to evaluating the museum's collection - which is inseparablefrom its architecture - the article is structured in three parts: rescuing the trajectory of thebuilding ́s design, reflecting on concepts of narratives and, finally, reading and analyzing thetexts recorded on the walls. The Museum's panels favor the identification of President JuscelinoKubitschek as the main person responsible for changing the Capital and the insertion of Brasíliain a long chronology that presents its construction as resulting from a yearning of the nation.